Oxidation Possibility of Manganese Dioxide Under Ambient Conditions - Xuan Dai, Trinh; Hong Con, Tran; Huong Giang, Pham; Viet, Cao (Asian Journal of Chemistry, 2015)
Fresh manganese dioxide material was prepared by soaking of pyrolusite grains in HCl solution to dissolve Fe(III) and Mn(II) ions to solution, then MnO2 and FeOOH were relied on oxidation and precipitation reactions to be coating back on the pyrolusite grains surface. The material was used for investigation of methylene blue oxidation process in water solution. In room temperature and at ambient pressure methylene blue was oxidized and decolourized in large range of pH value. The results showed that in acidic solution the manganese dioxide directly oxidize methylene blue and reduced itself into Mn(II) cation. In alkaline solution, manganese dioxide plays the role as an oxidation catalyst to oxidize methylene blue in presence of OH– ions and atmospheric oxygen. The mechanism of oxidation processes was also described.